Smart Dumpster: Development of Garbage Container Monitoring System to Support the Effectiveness of Garbage Disposal Transport in City(Case Study: Bandung City) - Benny Chaniago, Muhammad; Natsir Fajariadi, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
Development of urban infrastructure in Indonesia is followed by the phenomenon of urbanization, where some people hope to have a more prosperous life after moving from their rural. Therefore, there will be an increase in population and garbage production as an effect of urbanization itself. Unfortunately, the government does not provide appropriate facilities to overcome this problem. This has an impact on the deterioration quality of the environment, especially in transporting garbage in cities. Garbage becomes a serious problem that must be dealt with properly. Based on observations, garbage transportation is carried out regularly every day from homes or temporary shelters to final shelters. Basically, the method of transporting garbage is not effective enough in many aspects. The method, truck fuel, and also the type of truck used are several aspects that affect the effectiveness of garbage transportation. From the problems, this research was conducted to create a Smart Dumpster: Garbage Container Monitoring System by using the NodeMCU ESP82866 microcontroller, which is integrated with an ultrasonic sensor to identify the height of the garbage container. The data will be sent to the "Garbage Container Monitoring System," then processed, and finally it will be visualized on the map; it can also provide notifications. The system can help efficiently transport garbage by circling the city where the garbage container is full.